Effect of Interaction Straw Mulch and Organic Plus Fertilizer on Growth Soybean (Glycine max L.) - Nirdahayu Nirdahayu; La Ode Safuan; La Ode Afa; Gusti Ayu Kade Sutariati1 (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
The research aims to determine the interaction effect of the dose of straw mulch and organic plus fertilizer on the growth of soybean (Glycine max L.) on marginal dry land. This research was conducted from August to December 2021 at the research area of the Agriculture Faculty, Halu Oleo University, Kendari, Southeast Sulawesi. The research design used was a Split Plot arranged in a Randomized Block Design. The main plot was straw mulch (M) consisting of three levels, i.e., without straw mulch (M0), 4 tons ha-1 (M1), and 8 tons ha-1(M2); and Sub-plots were plus organic fertilizer (P) consisting of four levels, namely without plus organic fertilizer (P0); 2.5 tons ha-1(P1); 5 tons ha-1, (P2); and 7.5 tons ha-1 (P3). The measured variable is plant height, number of leaves, leaf area, dry weight of root, dry weight of shoot, and . The analysis of data using ANOVA, if The result of significant (Fhit> Ftab) continues with the DMRT test on α=0.05. The results showed that the treatment of Straw mulch 8 tons ha-1 and organic fertilizer 7.5 tons ha-1 resulted in the highest soybean growth.